The Correlation between Perception of Evangelism and Self-Concept to the Salvation Interests of Evangelism in GMII Filadelfia Surabaya - Teguh Santoso (Jurnal Missio Cristo, 2020)
Abstract: The fact shows that the interest of evangelism still needs to be improved. The purpose of this research is to testing the dependent variable which has connection to the evangelism interest, which is the perception toward evangelism and self concept to the salvation. Besides that, this research also wants to know about how the perception and self concept can give impact to the evangelism interest. The population of this research is the structural church servants (i.e. the pastor, elders, and committe) in GMII Filadelfia Surabaya. The amount of the servants are 46 people. This is a quantitative research that use questionnaire to get the result of the population. The questionnaire consists of the close questions. The close questions consist of the perception scale to the evangelism, self concept about salvation, and the evangelism interest, that were improved by the researcher. The analysis of double regresssion was used for testing the hypothesis of the research, based on the scale of the close questions. The testing of the hypothesis of the research shows the coefficient of the double correlation. (R) = 0,631, F = 13,556, p = 0,000 (p < 0,01). This means that there is a relationship perceptions of evangelism, self-concept toward salvation and evangelism interest. Evangelism interest can be explained by 63. 1% by perceptions of evangelism and self-concept toward salvation. Partially perceptions of evangelism has effective contribution of 55.4% and self-concept of the salvation of 66.1%. Based on these results, the servant in GMII Filadelfia Surabaya recommended to better understand the concept of self to safety. The spiritual adviser and pastor in GMII Filadelfia Surabaya shouldcontinue to preach and practice a lifestyle of evangelism as Christians.